Classical Rome - Clare, John D., 1952- (San Diego : Harcourt Brace & Co., 1993)
Recounts the struggles and triumphs of life in classical Rome.
"Gulliver Books.".
Includes index.
Booklist.
6.9
5-8.
5-8
Keywords: Rome -- Civilization -- Juvenile literature; Rome -- Civilization